Filling a significant gap in the cardiac ICU: implementation of individualised developmental care. (7th August 2017) - Butler, Samantha C.; Huyler, Kate; Kaza, Aditya; Rachwal, Chris
Abstract: Mortality rates among children with CHD have significantly declined, although the incidence of neurological abnormalities and neurodevelopmental impairment has increased. Research has focussed on outcomes, with limited attention on prevention and intervention. Although some developmental differences and challenges seen in children with CHD are explained by the cumulative effect of medical complications associated with CHD, many sequelae are not easily explained by medical complications alone. Although cardiac intensive care is lifesaving, it creates high levels of environmental and tactile stimulation, which potentially contribute to adverse neurodevelopmental outcomes. The therapeutic method of individualised developmental care, such as the Newborn Individualized Developmental Care and Assessment Program, provides early support and preventive intervention based on each child's behavioural signals of stress, comfort, and strength. Implementing developmental care practices in a cardiac ICU requires a thoughtful and well-planned approach to ensure successful adoption of practice changes. This paper reviews how developmental care was introduced in a paediatric inpatient cardiac service through multidisciplinary collaborative staff education, clinician support, child neurodevelopment assessment, parent support, and research initiatives. Given the known risk for children with CHD, cardiac medical professionals must shift their focus to not only assuring the child's survival but also optimising development through individualised developmental care in the cardiac ICU.